Integrating Conventional and Holistic Medicine for Precision and Personalized Diagnosis in Medical Laboratory Science - Andrew, Yashim-Nuhu; Yadock, Lusa Haruna; Kabir, Hauwa; Ogunkoya, Oluseun Funke; Akinloye, Oyetunde; Itodo, Sunday Ewaoche (British Journal of Healthcare and Medical Research, 2024)
The implementation of the combination of conventional and alternative medicine swing the new style in laboratory science known as personalized diagnosis or precision. Traditional approaches to disease mechanisms, such as genomic(-), proteomic-, and metabolomic analyses are informative. Lifestyle, environmental and psychosocial factors are frequently neglected. By performing a full assessment of individual health, gaps that are missed by standard medicine can be filled in holistic treatment. A combined approach of these methods is beneficial for a wide-ranging comprehension to address the disease manifold and enables based diagnostic and therapeutic concepts. The model seeks to improve diagnosis and treatment outcomes by considering both molecular determinants of health & disease, as well as contextual actors. Validating this integrative combination of technologies with a focus on personalized medicine will further post progress in improving clinical treatment.